The smart attendance of Microsoft team (SAMT2021) in an online learning classroom / Wan Normila Mohamad and Zahari Md Rodzi - Mohamad, Wan Normila; Md Rodzi, Zahari (2021)
Microsoft Teams has developed into an efficient platform for conducting online education and providing students with an ideal learning environment. Microsoft teams have numerous components, such as basic Microsoft team functions, discussions, evaluations, features, and attendance sheet. In this study we focus on the attendance sheet. There are some restrictions on the attendance sheet in Microsoft Teams in which it could not identify missing students. Second, it takes time to determine the length of a student's attendance in class due to the duplications of student names, and lastly, they lack monthly report compliance. In addressing these issues, we developed the smart attendance of microsoft team (SAMT2021) with an easy-to-use absence detection coordination. SAMT2021 can abstract the student's attendance frequency (in and out) of class report via the new smart attendance in comparison to Google Meet attendance and uFuture instant attendance. This smart attendance can directly and instantly connect to the WhatsApp chat to query and remind students on class absence. The anticipated result of SAMT2021 will efficiently enable lecturers to use these SAMT2021 systems and integrate them with INFOTECH and the Academic Affairs System.